Strategi Guru Akidah Akhlak Dalam Melakukan Preventif, Represif, Dan Kuratif Terkait Pemanfaatan Hp Oleh Santri Di Mts. S Pondok Pesantren Al- Mutaqin Balai Belo - Fadhdina, Irma Resti; Wati, Salmi; Charles, Charles; Arifmiboy, Arifmiboy (STAI Denpasar Bali, 2024)
This research discusses the strategies of Akidah Akhlak teachers at MTs.S PP Al-Mutaqin in facing the challenges of the globalization era, especially regarding the use of cellphones, changes in behavior and norms, criminal acts, and the instillation of Islamic values. Through a qualitative field approach, this research highlights the preventive, repressive and curative strategies implemented by teachers. In the context of using cellphones, teachers use direct advice, talk to parents, and provide sanctions as preventive, repressive and curative strategies. Apart from that, teachers face challenges related to behavior change with guidance, counseling and personal approaches. In dealing with criminal acts by students, teachers apply preventive strategies through direct advice and parental involvement. The repressive approach includes reprimands, sanctions, and a curative approach through a personal approach. Instilling Islamic values is carried out through the Islamic curriculum, fostering noble morals, and empowering Islamic education by involving extracurricular activities and parents. The challenges of globalization in learning are overcome by developing contextual curricula, increasing critical thinking skills, training in the use of technology, and supervision. The Aqidah Akhlak teacher at MTs.S PP Al-Mutaqin Balai Belo faces various challenges with a holistic strategy, involving various approaches. Obstacles include students' desire to follow trends and lack of fear of sanctions. This research suggestion includes involving more parties, such as parents, in formulating and implementing educational strategies